Pattern of brain activation during social cognitive tasks is related to social competence in siblings discordant for schizophrenia - Villarreal, Mirta Fabiana (2014)
Measures of social competence are closely related to actual community functioning in patients with schizophrenia. However, the neurobiological mechanisms underlying competence in schizophrenia are not fully understood. We hypothesized that social deficits in schizophrenia are explained, at least in part, by abnormally lateralized patterns of brain activation in response to tasks engaging social cognition, as compared to healthy individuals. We predicted such patterns would be partly heritable, and therefore affected in patients´ nonpsychotic siblings as well. We used a functional magnetic resonance image paradigm to characterize brain activation induced by theory of mind tasks, and two tests of social competence, the Test of Adaptive Behavior in Schizophrenia (TABS), and the Social Skills Performance Assessment (SSPA) in siblings discordant for schizophrenia and comparable healthy controls (n = 14 per group). Healthy individuals showed the strongest correlation between social competence and activation of right hemisphere structures involved in social cognitive processing, whereas in patients, the corre- lation pattern was lateralized to left hemisphere areas. Unaffected siblings of patients exhibited a pattern intermediate between the other groups. These results support the hypothesis that schizophrenia may be characterized by an abnormal functioning of nondominant hemisphere structures involved in the pro- cessing of socially salient information.